Organising creative interaction: spontaneous and routinised spheres of team creativity. Issue 4 (2nd October 2017) - Malmelin, Nando; Virta, Sari
ABSTRACT: The focus of this article is to develop theory and understanding about organisational creativity as a communicative phenomenon, especially from the viewpoint of creative interaction within teams. Interaction is central to creative processes, yet research concerning the subject has been scarce. Based on empirical analysis of a media organisation using the diary method and grounded theory, the article concentrates on understanding creative interaction as communication practices in an organisational context. The article contributes to the theory of creativity in organisations by introducing the spontaneous and routinised spheres of team-level creative interaction and by presenting a typology of six related communication practices.